Photochemical or electrochemical bond breaking – exploring the chemistry of (μ2-alkyne)Co2(CO)6 complexes using time-resolved infrared spectroscopy, spectro-electrochemical and density functional methods. Issue 39 (9th September 2019) - Manton, Jennifer C.; Cerpentier, Florian J. R.; Harvey, Emma C.; Clark, Ian P.; Greetham, Gregory M.; Long, Conor; Pryce, Mary T.
Abstract : The photoassisted Pauson–Khand reaction involves the formation of a high-spin diradical species and not CO loss as previously thought. Abstract : The photochemistry of (μ2 -CRCR′)Co2 (CO)6 complexes (R = pyrenyl, R′ = H; R = pyrenyl, R′ = ferrocenyl; R = ferrocenyl, R = H) was investigated by ps-time-resolved infrared spectroscopy at room temperature in dichloromethane solution. The main focus of these studies was to determine the primary photoprocess relevant to the light assisted Pauson–Khand reaction. These studies were supported by spectro-electrochemical investigations and density functional calculations which suggest that the primary process to initiate the Pauson–Khand reaction involves a homolytic cleavage of the Co–Co bond forming a high-spin diradical species and not CO-loss as previously thought.